Вихретоковый анизотропный термоэлектрический первичный преобразователь лучистого потока - Ascheulov, A. A.; Buchkovskiy, I. A.; Velichuk, D. D.; Romanyuk, I. S. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
An original design of eddy current anisotropic thermoelectric receiver non-selective radiation are the main parameters and shows the promise of its use.